2023
DOI: 10.1021/acssuschemeng.3c03887
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing and Freeze-Resistant Boat-Fruited Sterculia Seed Polysaccharide/Silk Fiber Hydrogel for Wearable Strain Sensors

Xiaokun Han,
Tianyun Lu,
He Wang
et al.

Abstract: This study introduces a sustainable bio-based hydrogel crafted from boat-fruited Sterculia seed polysaccharide (BF), silk fiber (SF), calcium chloride (CaCl2), and borax. The inherent hydrophilic groups and natural network structure of BF are conducive to the formation of a hydrogel with a high water content and a porous structure. The SF serves a dual role, providing structural support and acting as an antifreezing agent. The unique structure of this hydrogel is characterized by reversible dynamic cross-links… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Natural polysaccharide-based hydrogels have been recently gaining significant attention since they are biodegradable, environmentally friendly, and inexpensive . For example, Lu et al reported the fabrication of electrically conductive hydrogels for wearable strain sensors using a boat-fruited sterculia seed-based polysaccharide, silk fibers, calcium chloride, and borax. Ma et al synthesized biodegradable hydrogels for self-powered wearable sensors using natural straight-chain starch, calcium chloride, and Gly.…”
Section: Introductionmentioning
confidence: 99%
“…Natural polysaccharide-based hydrogels have been recently gaining significant attention since they are biodegradable, environmentally friendly, and inexpensive . For example, Lu et al reported the fabrication of electrically conductive hydrogels for wearable strain sensors using a boat-fruited sterculia seed-based polysaccharide, silk fibers, calcium chloride, and borax. Ma et al synthesized biodegradable hydrogels for self-powered wearable sensors using natural straight-chain starch, calcium chloride, and Gly.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al prepared a hydrogel with excellent self-adhesive and self-healing properties by using boronic ester bonds, coordination bonds, and hydrogen bonds. The healed hydrogel still could be used as a flexible strain sensor to monitor electrical signals at different strains . Furthermore, conventional water-based hydrogels tend to inevitably freeze and lose inherent flexibility at subzero temperatures.…”
Section: Introductionmentioning
confidence: 99%